Policy Discourses: Shifting the Burden of Healthcare from the State to the Market in the Kingdom of Saudi Arabia - Redwanur Rahman PhD; Mohammad Asif Salam PhD (SAGE Publishing, 2021)
Saudi Arabia has modified from a predominantly free, public, and comprehensive system under a welfare model to more of a mixed-economy model of healthcare. The welfare state slowly moved to a liberal model, emphasizing market forces to dominate in the provision of healthcare and the private sector was trusted to provide a better provision of healthcare. The country has to confront enormous problems in the health sector due to population growth, lifestyle changes, the shift of disease patterns, elevated expectations, escalated healthcare costs, limited infrastructure and resources, and poor management practice in the provision of healthcare. Moreover, the government has been emphasizing the need to bring in private sector investment to improve quality and efficiency, development of manpower, and standardization of services. As the current pattern of healthcare is unsustainable, the country is planning to restructure the present healthcare system toward institutionalizing it to meet future challenges. The governments must make an appropriate amount of effort to build their healthcare systems by transforming and modifying the challenges faced by society and its political-economic systems. The government should encourage equity, and fairness in the provision of healthcare.